Results of a phase I dose escalation study of eltrombopag in patients with advanced soft tissue sarcoma receiving doxorubicin and ifosfamide - Chawla, Sant P (BioMed Central, 2013)
BACKGROUND: The objective of this Phase I dose escalation study was to explore the safety and tolerability of eltrombopag, an oral, nonpeptide, thrombopoietin receptor agonist, in patients with advanced soft tissue sarcoma (STS) and thrombocytopenia due to treatment with doxorubicin and ifosfamide (AI) combination chemotherapy. METHODS: Patients aged 18 or older with histologically confirmed, locally advanced or metastatic STS were treated with 1 cycle of AI followed by AI with eltrombopag starting at Cycle 2, using 2 different dosing schedules. The study design included an eltrombopag dose escalation phase starting at 75 mg daily to determine the optimal biological dose (OBD). RESULTS: Eighteen patients were enrolled and 15 received at least 1 dose of chemotherapy; 3 patients withdrew prior to receiving eltrombopag. Seven, 4, and 1 patients received 75 mg, 100 mg, and 150 mg eltrombopag daily, respectively. No dose-limiting toxicities were reported. Due to slow recruitment, the study was closed prior to identifying an OBD. The most common hematologic adverse events (AEs) were thrombocytopenia (80%), neutropenia (73%), and anemia (67%). The most common nonhematologic AEs were fatigue (53%), alanine aminotransferase increased, constipation, and nausea (47% each). Eleven of 12 patients who received eltrombopag completed at least 2 chemotherapy cycles; all had increased platelet counts on Day 1 of Cycle 2 (cycle with eltrombopag) compared to Day 1 of Cycle 1 (cycle without eltrombopag). CONCLUSIONS: Although data are limited, safety data were consistent with the known toxicities of AI combination chemotherapy or the side effect profile of eltrombopag seen in other studies. Available data suggest a potential pre- and post-chemotherapy dosing scheme for eltrombopag when administered with AI chemotherapy, and support further investigation of eltrombopag treatment in patients with chemotherapy-induced thrombocytopenia.